Numerical Assessment on Training Motivation, Syllabus and Instructor’s Roles in Military Training Program Using PLS - Noor Azmi Mohd Zainol; Fazli Abd Hamid; Ahmad Azan Ridzuan; Daud Mohamed Salleh (American Scientific Publishers, 2018)
Training management literature emphasized the designing of training program consist of three important elements: (1) training syllabus; (2) instructors’ roles; and (3) superiors’ support, which may lead to a high impact of training transfer in organizations. However, the role of training motivation as a mediator is given less explanation in the training program. Therefore, the aim of this research is to investigate and quantify the effect of training motivation in the military training. The measurements were using 329 usable questionnaires gathered from Royal Malay Regiment personnel of Malaysian Army. The outcomes of hypotheses testing showed these interesting findings: training motivation does act as an important mediating variable between training syllabus and instructors’ roles in the relationship with training transfer, whilst there are no mediation effect in relationship between superiors’ support and training transfer. Further, discussion, implications and conclusion are elaborated.